2010
DOI: 10.3109/10641950903572282
|View full text |Cite
|
Sign up to set email alerts
|

Are Early and Late Preeclampsia Distinct Subclasses of the Disease—What Does the Placenta Reveal?

Abstract: The early- and late-onset preeclampsia placentas showed clear histopathological differences, whereas late-onset preeclampsia and normal term placentas differed less. These findings support the contention that early- and late-onset preeclampsia are different subclasses of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 22 publications
1
56
0
3
Order By: Relevance
“…This study meta-analyzes data from publications using this classification, and demonstrates a higher prevalence of both villous and vascular histopathological lesions in the placentae of PE pregnancies than in the placentae of normal pregnancies. The latter finding is in keeping with those of previous studies conducted prior to agreed Ruiz-Quiñonez (2014) 11 Devisme (2013) 7 Maloney (2012) 6 Pathak (2011) 10 Ogge (2011) 5 van Der Merwe (2010) 9 Vinnars (2010) 8 Kos (2005) 4 Devisme (2013) 7 Maloney (2012) 6 Ogge (2011) 5 Kos (2005) Ruiz-Quiñonez (2014) 11 Pathak (2011) 10 van Der Merwe (2010) 9 Vinnars (2010) classifications or when using different histopathological classifications for placental lesions.…”
Section: Association Of Placental Lesions With Pesupporting
confidence: 81%
See 2 more Smart Citations
“…This study meta-analyzes data from publications using this classification, and demonstrates a higher prevalence of both villous and vascular histopathological lesions in the placentae of PE pregnancies than in the placentae of normal pregnancies. The latter finding is in keeping with those of previous studies conducted prior to agreed Ruiz-Quiñonez (2014) 11 Devisme (2013) 7 Maloney (2012) 6 Pathak (2011) 10 Ogge (2011) 5 van Der Merwe (2010) 9 Vinnars (2010) 8 Kos (2005) 4 Devisme (2013) 7 Maloney (2012) 6 Ogge (2011) 5 Kos (2005) Ruiz-Quiñonez (2014) 11 Pathak (2011) 10 van Der Merwe (2010) 9 Vinnars (2010) classifications or when using different histopathological classifications for placental lesions.…”
Section: Association Of Placental Lesions With Pesupporting
confidence: 81%
“…Devisme (2013) 7 Maloney (2012) 6 Ogge (2011) 5 van Der Merwe (2010) 9 Vinnars (2010) 8 Devisme (2013) 7 Maloney (2012) 6 Ogge (2011) Figure 4 Forest plots of odds ratios (ORs) (random-effects model) for vascular lesions in pregnancies complicated by pre-eclampsia and normotensive pregnancies, for all studies (a) and for blinded (b) and unblinded (c) studies. Only first author given for each study.…”
Section: Pooled and Population Prevalence Of Histological Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26] It has also been suggested that women with chronic hypertension or diabetes mellitus develop PE in the context of smaller increments of sFlt and sEng, because there is already preexisting maternal endothelial cell dysfunction. 27 Our finding of more significant alterations in angiogenic factors in early versus late-onset SPE are consistent with reports that more severe placental dysfunction distinguishes early onset from late-onset SPE in women without preexisting hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it is thought that early-onset PE involves a placental defect, which is not as evident in late-onset PE. It appears that late-onset PE involved a different inflammatory component [34]. The impaired trophoblastic invasion of the placental bed and the following cascade in the early onset of PE might already determine the severity of the disease, and external factors like TRAP become less obvious.…”
Section: Discussionmentioning
confidence: 99%